The Prevalence and Characteristics of Psoriatic Arthritis in Patients With Psoriasis in a Tertiary Hospital - Nilay ÇINAR,; Hatice BODUR,; Filiz ESER,; Ülker GÜL,; Müzeyyen GÖNÜL,; Işıl Deniz OĞUZ, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate psoriatic arthritis (PsA) prevalence in patients with psoriasis (Ps), and compare clinical and laboratory characteristics of patients with or without PsA. Patients and methods: A total of 126 patients (59 males, 67 females; mean age 45.6±13.8 years; range 18 to 82 years) with Ps who applied to Dermatology Outpatient Clinic between October 2009 and September 2010 were included in this study. The patients were screened for PsA using Classification of Psoriatic Arthritis criteria. The patients classified as PsA were grouped according to Moll and Wright criteria. Enthesopathy was evaluated according to Maastricht Ankylosing Spondylitis Enthesis score. Psoriasis Area and Severity Index scores were calculated by the same dermatologist. Results: The prevalence of PsA was 25.4%. Ps duration was significantly longer in the group with PsA. The most common type was asymmetrical oligoarticular type (53.1%). Compared to previous studies, the rate of isolated spondyloarthropahty was higher in our study (21.9%). Nail involvement, Psoriasis Area and Severity Index score, mean erythrocyte sedimentation rate, and C-reactive protein values were significantly higher in the group with PsA. Conclusion: High rate of isolated spondyloarthropahty in patients with PsA indicates that PsA must be kept in mind in the differential diagnosis of seronegative spondyloarthropathies. The fact that nail involvement is seen more frequently in patients with arthritis may assist in screening of PsA in patients with Ps. In addition, our results showing a higher probability of PsA development in patients with more severe skin lesions and a higher probability of arthritis development in patients with long lasting Ps may guide clinicians in terms of the probability of arthritis development in patients with Ps.